等著被說出的軀體與病患意義: Waiting to be Uttered - QIU, Hongzhong (International Journal of Chinese & Comparative Philosophy of Medicine, 2015)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. Sun’s article is a useful exploration of the body ethics model of medicine. However, a body is not the equivalent of a person—the body is waiting to utter its meaning. This commentary, which adopts a phenomenological perspective, discusses different ways of treating the body and of interrogating the senses of the body understood by patients and doctors. Divergent such senses influence the doctor-patient relationship in quite distinct ways. To establish a new clinical model, this commentary holds that we need to pay greater attention to the epistemology and methodology of somatic phenomenology, which can inspire us to understand the comprehensive significance of the body for medicine. DOWNLOAD HISTORY | This article has been downloaded 35 times in Digital Commons before migrating into this platform.